Hubungan Pola Asuh Orang Tua dengan Kemampuan Membaca Anak Usia Dini di Jorong VI Parit Panjang Nagari Lubuk Basung - Tistanawaty, Tistanawaty; Azizah, Zahratul (Jurnal Family Education, 2025)
This research was motivated by the low reading ability of young children in Jorong VI Parit Panjang Nagari Lubuk Basung, this is thought to be due to children's environmental factors, namely parents who apply inappropriate parenting patterns to young children. This research aims to (1) describe the parenting patterns of parents of early childhood in Jorong VI Parit Panjang. (2) Description of the reading abilities of early childhood children in Jorong VI Parit Panjang. (3) The relationship between parenting styles and the reading ability of early childhood in Jorong VI Parit Panjang. This type of research uses quantitative correlation research methods. The population of this study was 25 people with the criteria being that they were registered as residents in Jorong VI Parit Panjang and parents who had children aged 5-6 years. In this research sampling, because the population was less than 100 people, the entire population was sampled, namely 25 people. The type of instrument that will be applied in this research is a questionnaire as a data collection tool with a Likert scale. Data analysis uses the percentage formula and Spearman rho correlation. The results of the research show that: 1) The description of parenting patterns of parents in Jorong VI Parit Panjang can be categorized as low. This is proven by the dominant respondents' answers, namely disagreeing; 2) The description of the reading ability of young children in Jorong VI Parit Panjang can be categorized as low. This is proven by the respondents' answers which dominate, namely disagreeing. 3) There is a significant relationship between parenting patterns and the reading ability of young children in Jorong VI Parit Panjang. This is proven by r count = 0.488 and this value is compared with r table = 0.4005 with a significance level of 5% and n=25. From these results it is obtained that r count > r table.